The galaxy population of Abell 1367: The stellar mass-metallicity relation - M. Mouhcine (2018)
Using wide baseline broad-band photometry, we analyse the stellar population properties of a sample of 72 galaxies, spanning a wide range of stellar masses and morphological types, in the nearby spiral-rich and dynamically young galaxy cluster Abell 1367. The sample galaxies are distributed from the cluster centre out to approximately half the cluster Abell radius. The optical/near-infrared colours are compared with simple stellar population synthesis models from which the luminosity-weighted stellar population ages and metallicities are determined. The locus of the colours of elliptical galaxies traces a sequence of varying metallicity at a narrow range of luminosity-weighted stellar ages. Lenticular galaxies in the red sequence, however, exhibit a substantial spread of luminosity-weighted stellar metallicities and ages. For red-sequence lenticular galaxies and blue cloud galaxies, low-mass galaxies tend to be on average dominated by stellar populations of younger luminosity-weighted ages. Sample galaxies exhibit a strong correlation between integrated stellar mass and luminosity-weighted stellar metallicity. Galaxies with signs of morphological disturbance and ongoing star formation activity, tend to be underabundant with respect to passive galaxies in the red sequence of comparable stellar masses. We argue that this could be due to tidally driven gas flows towards the star-forming regions, carrying less enriched gas and diluting the pre-existing gas to produce younger stellar populations with lower metallicities than would be obtained prior to the interaction. Finally, we find no statistically significant evidence for changes in the luminosity-weighted ages and metallicities for either red-sequence or blue-cloud galaxies, at fixed stellar mass, with location within the cluster. © 2010 The Authors Monthly Notices of the Royal Astronomical Society © 2010 RAS.